Comparison of methods and TAT assessment: Volumetric AQUIOS CL and bead‐based FACS CANTO II cytometers. Issue 4 (15th February 2017) - Grossi, Valentina; Infantino, Maria; Meacci, Francesca; Bellio, Emanuele; Bellio, Valerio; Ciotta, Giovanna; Priami, Fiorella; Sarzi‐Puttini, Piercarlo; Atzeni, Fabiola; Li Gobbi, Francesca; Damiani, Arianna; Benucci, Maurizio; et al.
Abstract : Background: Measurement of lymphocyte subpopulations is a crucial parameter in the diagnosis and monitoring of therapy in a wide variety of clinical conditions. We compared different flow cytometry‐based methods to determine lymphocyte subsets counts of routine samples by volumetric AQUIOS CL (Beckman Coulter) and bead‐based FACS CANTO II (BD Biosciences) cytometers. We evaluated the possible decrease of the labor intensive technical work using the fully automated AQUIOS CL system in the pre and post analytical steps in comparison with our routine flow cytometer FACS CANTO II, toward the reduction of laboratory analytical turnaround time (TAT). Methods: The analytical performance of AQUIOS CL flow cytometer compared with FACS CANTO II was evaluated testing 224 routine samples, attending the Immunology and Allergology Laboratory Unit, S. Giovanni di Dio Hospital, (Florence, Italy) between September and October 2015. Results: Bland–Altman plot of the differences between the two methods showed an excellent agreement for absolute and percentage counts. Furthermore, the study showed that automated AQUIOS CL system is simple to be used during all analytical steps with a reduction of TAT. Conclusion: In routine conditions, AQUIOS CL flow cytometer could be a suitable tool for subpopulations subset analysis. © 2017 International Clinical Cytometry Society